CORRELATION BETWEEN TRANS-RECTAL ULTRASOUND GUIDED (TRUS) BIOPSIES REPORTING STANDARDS AND MULTI-DISCIPLINARY TEAM DISCUSSIONS, IN THE MANAGEMENT OF PROSTATE CANCER. (February 2015) - Lin, Zhiliang Caleb; Tan, Jie Wen Bryan; Ranasinghe, Weranja; Shahbaz, Shekib; McCahy, Philip
Abstract : Aim: To investigate the reporting standards of TRUS biopsies and examine the effects on treatment decisions and related costs in low to intermediate-risk prostate cancer (PCa) Methods: 675 patients undergoing TRUS biopsies at Monash Health from May 2010–2014 were retrospectively reviewed and stratified using the D'Amico risk classification, of which 218 fell into low and intermediate risk categories. Decisions to discuss patients at multi-disciplinary-team (MDT) meetings and further urological consultations were established by reviewing scanned medical and pathology reports. Results: Of the 218 intermediate risk PCa, 144 (66.1%) were reported with a percentage of tumour involvement per biopsy core, 43 (19.7%) were reported with measurements of tumour involvement and 31 (14.2%) only included a positive finding for cancer. Conclusion and discussion: Current international reporting guidelines are not being used by some pathologists in Australia. Variation in TRUS biopsy reporting may affect the management of patients. In addition, this may increase patient anxiety by delaying treatment. In the intermediate risk category, the pathology report plays an essential role in determining the need for MDT. As such we recommend a standardisation of TRUS biopsy reporting standards to aid in standardised treatment of patients.